KAP1/TRIM28: Transcriptional Activator and/or Repressor of Viral and Cellular Programs? - Randolph, Keyera; Hyder, Usman; D’Orso, Iván (Frontiers in Cellular and Infection Microbiology, 2022)
Several transcriptional and epigenetic regulators have been functionally linked to the control of viral and cellular gene expression programs. One such regulator is Krüppel-associated box (KRAB)-associated protein 1 (KAP1: also named TRIM28 or TIF1β), which has been extensively studied in the past three decades. Here we offer an up-to date review of its various functions in a diversity of contexts. We first summarize the discovery of KAP1 repression of endogenous retroviruses during development. We then deliberate evidence in the literature suggesting KAP1 is both an activator and repressor of HIV-1 transcription and discuss experimental differences and limitations of previous studies. Finally, we discuss KAP1 regulation of DNA and RNA viruses, and then expand on KAP1 control of cellular responses and immune functions. While KAP1 positive and negative regulation of viral and cellular transcriptional programs is vastly documented, our mechanistic understanding remains narrow. We thus propose that precision genetic tools to reveal direct KAP1 functions in gene regulation will be required to not only illuminate new biology but also provide the foundation to translate the basic discoveries from the bench to the clinics.